The Basel Capital Accords in Developing Countries Challenges for Development Finance - Gottschalk, R.; Gottschalk, R. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
This book is about the new capital adequacy framework – known as Basel II – approved by the Basel Committee in 2004. It aims to discuss Basel II implementation in different categories of developing countries, including emerging market economies, such as Brazil and low-income countries such as Ethiopia and Zambia.